22 Evaluating the content of choosing wisely recommendations and the prevalence of interdisciplinary finger pointing. (20th August 2018) - Zadro, Joshua; Harris, Ian; Maher, Christopher
Abstract : Objectives: The aim of this study is to evaluate the content of existing Choosing Wisely lists and determine the proportion of Choosing Wisely recommendations that discuss tests or treatments; whether recommendations are worded appropriately (i.e. target a reduction in low-value care and provide recommendations that are actionable and direct); and whether recommendations targeting low-value income generating treatments are directed towards society members or non-members ('finger pointing'). Method: We will perform a content analysis of all Choosing Wisely recommendations, extracting recommendations from Choosing Wisely websites and The Diana (Dissemination of Initiatives to ANalyse Appropriateness) in Healthcare website (including data on the professional society, year and country of the recommendation). Two researchers will independently apply the following checklist to determine the frequency of recommendations that are tests or treatments; recommended 'for' or 'against' a procedure ('do' vs. 'don't'); include an alternative when advising against a procedure; are direct ('don't') or indirect ('consider avoiding', 'don't routinely', etc.); and advise against an income generating treatment (and whether the treatment is typically performed by members, non-members, or both). Disagreements will be resolved by discussion or consultation with a third reviewer if necessary. The frequency of coded data will be presented using descriptive statistics (counts and percentages). Results: We found 1, 265 Choosing Wisely recommendations across the United States (n=535, 42.3%), Canada (n=297, 23.5%), Italy (n=175, 13.8%), Australia (n=172, 13.6%), the United Kingdom (n=56, 4.4%) and the Netherlands (n=30, 2.4%). There were 200 (15.8%) recommendations from surgical societies, 155 (12.3%) from allied health or nursing societies, 131 (10.4%) from general medical societies (e.g. palliative care, geriatrics, internal medicine), and 50 (4.0%) from emergency medicine or critical care societies. Coding of the recommendations is ongoing and we will present the full results of the analyses at the conference. Conclusions: There are currently 1, 265 Choosing Wisely recommendations published worldwide; but there is yet to be an evaluation of their content. The wording of Choosing Wisely recommendations could support or prevent adoption, so our findings are the first step towards improving recommendations to facilitate their use in practice. Our study will also determine whether recommendations are adequately covering low-value treatments (particularly income generating treatments), and whether these recommendations are directed to members or non-members. Healthcare professionals are 10 times more likely to discuss low-value tests with their patients compared to low-value treatments; possibly reflecting concerns about losing income. Our findings could have strong implications for creating transparency in Choosing Wisely and ensuring that societies aren't using recommendations directed at non-members ('finger pointing') to avoid publishing recommendations against low-value treatments that could affect their members' income.